The Patterns and Social Determinants of Breastfeeding in 12 Selected Regions in China: A Population-Based Cross-Sectional Study. (August 2020) - Fang, Zhe; Liu, Yuning; Wang, Hanyu; Tang, Kun
Background: With rapid industrialization and urbanization, there is a growing need for women to enter the workforce, and affluent people are drawn to the infant formula market. The breastfeeding rates in China are below the optimal level. Large scale quantitative research studying breastfeeding practices after 2015 in China are lacking. Research aim: We aimed to (1) explore the latest patterns and (2) identify the determinants of breastfeeding in China. Methods: The study was a population-based, cross-sectional survey. A multi-stage sampling technique was adopted for the selection of participants. We recruited 10, 408 mothers with children under 12 months old, in 12 regions of China, and conducted a questionnaire survey about breastfeeding patterns. The associations between social and biophysical determinants and breastfeeding outcomes were analyzed using a logistic regression model. Results: The exclusive breastfeeding rate was 29.32% ( n = 3, 052) decreasing from 32.71% ( n = 3, 404) to 15.83% ( n = 1, 648) among children aged 0–5 months. Cesarean section had a negative association with early breastfeeding initiation ( OR = .33, 95% CI [.30, .36]), exclusive breastfeeding ( OR = .78, 95% CI [.69, .89]), and predominant breastfeeding ( OR = .73, 95% CI [.65, .83]). Compared to participants with an annual household income lower than 40, 000 Yuan ($5, 817 USD), those with over 100, 000 Yuan ($14, 542 USD) had an OR of .78 (95% CI [.67, .90]) in exclusive breastfeeding. Compared with illiterate and unemployed groups, middle/high school education and a current work status, respectively, were associated with a lower likelihood of exclusive breastfeeding ( OR = .73, 95% CI [.63, .84]; OR = .58, 95% CI [.37, .89]). Conclusions: The prevalence of breastfeeding in 12 selected regions in China was low and interventions focusing on the targeted population should be strengthened.